Combining Bulk and Single Cell RNA-Sequencing Data to Identify Hub Genes of Fibroblasts in Dilated Cardiomyopathy - Huang X; Zhao X; Li Y; Feng Y; Zhang G; Wang Q; Xu C (Dove Medical Press, 2024)
Xiaoyan Huang,1,2 Xiangrong Zhao,1,2 Yaping Li,1,2 Yangmeng Feng,1,2 Guoan Zhang,3 Qiyu Wang,4 Cuixiang Xu1,2 1Shaanxi Provincial Key Laboratory of Infection and Immune Diseases, Shaanxi Provincial People's Hospital, Xi'an, People's Republic of China; 2Shaanxi Engineering Research Center of Cell Immunology, Shaanxi Provincial People's Hospital, Xi'an, People's Republic of China; 3Department of Cardiovascular Surgery, Shaanxi Provincial People's Hospital, Xi'an, People's Republic of China; 4Department of Graduate School, Yan'an University, Yan'an, People's Republic of ChinaCorrespondence: Cuixiang Xu, Email xucuixiang1129@163.comBackground: Dilated cardiomyopathy (DCM) is the second leading cause of heart failure, with intricate pathophysiological underpinnings. In order to shed fresh light on the mechanistic research of DCM, we combined bulk RNA-seq and single-cell RNA-seq (scRNA-seq) data to examine significant cells and genes implicated in the disease.Methods: This analysis employed publicly accessible bulk RNA-seq and scRNA-seq DCM datasets. The scRNA-seq data underwent normalization, principal component, and t-distribution stochastic neighbor embedding analysis. Cell-to-cell communication networks and activity analysis were conducted using CellChat. Utilizing enrichment analysis, the marker genes' role in the active cells was evaluated. After screening by limma software and weighted gene co-expression network analysis, the differentially expressed genes (DEGs) served as hub genes. Furthermore, these hub genes were subjected to immunological studies, transcription factor expression, and gene set enrichment. Lastly, the expression of the four hub genes and their connection to DCM were verified using the rat models.Results: Fibroblasts and monocytes were chosen as hub cells from among the eight identified cell clusters; their marker genes intersected with DEGs to yield six hub genes. In addition, the six hub genes and the essential module genes intersected to yield four essential genes (ASPN, SFRP4, LUM, and FRZB) that were connected to the Wnt signaling pathway and highly expressed in fibroblast. The four hub DEGs had an expression pattern in the DCM rat model experiment results that was in line with the findings of the bioinformatics study. Additionally, there was a strong correlation between decreased cardiac function and the up-regulation of ASPN, SFRP4, LUM, and FRZB.Conclusion: Ultimately, bulk RNA-seq and scRNA-seq data identified fibroblasts and monocytes as the main cell types implicated in DCM. The highly expressed genes ASPN, FRZB, LUM, and SFRP4 in fibroblasts may aid in the mechanistic investigation of DCM.Keywords: dilated cardiomyopathy, single cell RNA-seq, bulk RNA-seq, weighted gene co-expression network analysis, wnt signaling pathway, fibroblasts